STUDING RADIOECOLOGICAL PROBLEMS IN THE CASPIAN REGION - Otar Gerzmava; Rukhsara Alieva; Niazy Hajizade (European Scientific Journal, ESJ, 2016)
In the present article there is given analysis of materials about study of the natural and anthropogenic radio nuclides in the Caspian region for the creation of a monitoring network and the assessment of radiological hazards with determinations of compliance to international health and safety standards. Radionuclides are come across in different districts of the Caspian territory and their radiation give way to the realization of the ionizing radiation. Also there have bееn shown ways of nature protection оn the ecological and legal base to prevent water pollution. In the Caspian districts where more than 3 million people live, the investigations carried out about the radiation levels do not draw a clear picture about the environmental pollution.